2017
DOI: 10.1177/1550147717699412
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a low-power wide-area network based on LoRa technology: Doppler robustness, scalability, and coverage

Abstract: The article provides an analysis and reports experimental validation of the various performance metrics of the LoRa low-power wide-area network technology. The LoRa modulation is based on chirp spread spectrum, which enables use of low-quality oscillators in the end device, and to make the synchronization faster and more reliable. Moreover, LoRa technology provides over 150 dB link budget, providing good coverage. Therefore, LoRa seems to be quite a promising option for implementing communication in many diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
230
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(243 citation statements)
references
References 11 publications
7
230
1
5
Order By: Relevance
“…In Malaysia, Lora was tested using 433MHz where this frequency is under the unlicensed spectrum in the country. Several studies have been conducted on LoRa performance at 868 MHz modulation [4][5].A comparison of LoRa in 868 MHz and 433 MHz was done by [6] in Europe.In urban environment, the IoT is aiming to develop smart cities with capabilities to provide a number of benefits in the management and optimization of traditional public services such as transport, parking system, lighting, tank level monitors, surveillance and so forth [7][8]. Other than urban application, LoRa-based network has also been deployed in maritime setting [4].However, not much work has been done up to this date on LoRa propagation performance in the tropical climate environments.…”
Section: Previous Workmentioning
confidence: 99%
“…In Malaysia, Lora was tested using 433MHz where this frequency is under the unlicensed spectrum in the country. Several studies have been conducted on LoRa performance at 868 MHz modulation [4][5].A comparison of LoRa in 868 MHz and 433 MHz was done by [6] in Europe.In urban environment, the IoT is aiming to develop smart cities with capabilities to provide a number of benefits in the management and optimization of traditional public services such as transport, parking system, lighting, tank level monitors, surveillance and so forth [7][8]. Other than urban application, LoRa-based network has also been deployed in maritime setting [4].However, not much work has been done up to this date on LoRa propagation performance in the tropical climate environments.…”
Section: Previous Workmentioning
confidence: 99%
“…Detailed description of the physical layer and medium access control of the two LPWAN technologies, the deployment of which is currently actively ongoing, namely Sigfox and LoRa, has been presented in [8]. In our previous studies we have focused on the different aspects of the LoRa LPWAN technology and reported the results for the technology scalability and capacity analysis in [9], the outdoor coverage measurements and channel characterization in [10], and the effect of mobility and Doppler robustness on communication performance in [11]. In [12] we have initially proposed the possibility of employing the LoRa LPWAN technology for wearables and have reported the first results, which are expanded further in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the Ultra Narrow Band (UNB) modulation, CSS uses a wider band and in the Industrial, Scientific and Medical (ISM) bands from region to region, for example, 868 MHz in Europe, 915 MHz in America. In the 868 MHz band, LoRaWAN specifications enable 8 physical options: six are based on LoRa modulation with a bandwidth of 125 kHz and the SF between 7 and 12, one is based on LoRa modulation with 250 kHz bandwidth and SF 7 and the last one is based on the Gaussian Frequency Shift Keying (GFSK) with a data rate of 50 kbps . In LoRaWAN and SigFox, end nodes can communicate only with gateways and they cannot send packets directly to other end nodes.…”
Section: Background On Lpwansmentioning
confidence: 99%